1994
DOI: 10.1149/1.2054836
|View full text |Cite
|
Sign up to set email alerts
|

High Ammonia Sensitive Semiconductor Gas Sensors with Double‐Layer Structure and Interface Electrodes

Abstract: firms the applicability Li § gel electrolyte for optical devices. In addition, this electrolyte has a very wide electrochemical stability window (i.e., ranging from 0 to about 5 V vs. Li, see Fig. 9), which gives assurance of an unusual 1657 (1990).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(47 citation statements)
references
References 2 publications
1
46
0
Order By: Relevance
“…Various bulk-heterojunction photovoltaic devices have been made in recent years using polymer composites [1] or conjugated polymers with fullerenes. [2,4±6] Moreover, polymers have been blended with CdSe nanoparticles to create hybrid solar cells.…”
Section: Methodsmentioning
confidence: 99%
“…Various bulk-heterojunction photovoltaic devices have been made in recent years using polymer composites [1] or conjugated polymers with fullerenes. [2,4±6] Moreover, polymers have been blended with CdSe nanoparticles to create hybrid solar cells.…”
Section: Methodsmentioning
confidence: 99%
“…It is found that although all gas molecules can influence the electronic structure of AGNRs, only NH 3 molecule adsorption can modify the conductance of AGNRs remarkably by acting as donors while other gas molecules have little effect on conductance. This property can be utilized to detect NH 3 out of other common gases, which is requisite and significant in industrial, medical, and living environments [32].…”
Section: Introductionmentioning
confidence: 99%
“…When the sensor material is exposed to vapors of ammonia, the superficial reactions of NH 3 molecules with the oxygen species caused more electrons to return to the conduction band because ammonia acting as the electron donor. The surface reactions between the NH 3 and the sensor material can be described as follows [18][19][20][21] where O − (ads), NO 2 − (ads), and NO 3 − (ads) represent negatively charged chemisorbed species, and e − free electrons available for electrical conduction. The relations means that when the sensor is exposed to NH 3 containing gas, electrons trapped by the adsorptive states will be released, leading to a decrease in sensor resistance, as experimentally observed (Fig.…”
Section: Resultsmentioning
confidence: 99%